25-OH vitamin D threshold for optimal bone mineral density in elderly patients with chronic kidney disease - Roy, Debajyoti; Ng, Chee Yong; Kog, Zheng Xi; Yeon, Wenxiang; Poh, Cheng Boon; Koduri, Sreekanth; Chionh, Chang Yin; Sultana, Rehena; Hai Kiat Puar, Troy (Frontiers in Aging, 2022)
Introduction: Vitamin D deficiency is common in chronic kidney disease (CKD) and is associated with lower bone mineral density (BMD), decreased muscle strength, and increased hip fracture risk. Guidelines have suggested targeting 25-OH vitamin D (25(OH)D) levels between 20 and 30 ng/ml. However, vitamin D metabolism is altered in CKD, and threshold levels for optimal BMD are unknown. Methods: We included 1097 patients with hip fractures. CKD was defined as estimated glomerular filtration rate <60 ml/min/1.73 m (Mucsi et al., Clin. Nephrol., 2005, 64(4), 288–294) and low BMD defined as T score ≤ −2.5 at femoral neck. We assessed the association of 25(OH)D with low BMD in patients with and without CKD: using the conventional threshold 25(OH)D < 30 ng/dl, as well as a new threshold. Results: CKD was present in 479 (44%) patients. Using a threshold of 25(OH)D < 30 ng/ml, there were no significant differences in patients with CKD and low BMD when compared to the other groups. We identified 27 ng/ml as a better threshold with the Youden index. Using 25(OH)D < 27 ng/ml as a threshold, 360 of 482 patients (74.7%) with low 25(OH)D had low BMD, compared to only 185/276 (67%) of patients with adequate vitamin D, p = 0.02, which was irrespective of the presence or absence of CKD. Furthermore, patients with CKD and 25(OH)D < 27 ng/ml had a higher odds ratio of mortality upon follow-up, 1.61, 95% CI: 1.08–2.39, compared to those with CKD and 25(OH)D ≥ 27 ng/ml. Conclusion: We find that 25(OH)D < 27 ng/ml is associated with low BMD in patients with and without CKD. Further prospective studies targeting vitamin D repletion to at least 27 ng/ml and the outcome of hip fractures will be useful to validate these findings.